2021
DOI: 10.1039/d1tb00469g
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated polymer nanostructures displaying highly photoactivated antimicrobial and antibiofilm functionalities

Abstract: This work report the use of conjugated polymer nanostructures (CPNs) as photoactivated antimicrobial compounds against gram-positive and gram-negative microorganisms. Two representative CPNs of polythiophene (PEDOT) and polyaniline (PANI) were prepared...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition to their use in various electrochemical sensing platforms, functionalized PEDOT nanostructures are promising candidates for applications in biology, electronics, and materials science. There have been a few reports on the use of electropolymerization to deposit conducting polymers in the active channel areas of OECTs. Nevertheless, tailoring functionalized PEDOT nanostructures in the active channel area of OECT devices and investigating the effects of such nanostructures on sensing, particularly of sweat biomarkers, has remained unexplored. We are unaware of any previous investigations into nanostructure engineering through template-free electropolymerization or of the use of nanostructures of functionalized PEDOT derivatives in OECT channel areas to target the detection of cortisol in sweat, with wearable applications in mind.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their use in various electrochemical sensing platforms, functionalized PEDOT nanostructures are promising candidates for applications in biology, electronics, and materials science. There have been a few reports on the use of electropolymerization to deposit conducting polymers in the active channel areas of OECTs. Nevertheless, tailoring functionalized PEDOT nanostructures in the active channel area of OECT devices and investigating the effects of such nanostructures on sensing, particularly of sweat biomarkers, has remained unexplored. We are unaware of any previous investigations into nanostructure engineering through template-free electropolymerization or of the use of nanostructures of functionalized PEDOT derivatives in OECT channel areas to target the detection of cortisol in sweat, with wearable applications in mind.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ghosh and co-workers reported photocatalytic bacterial inactivation by employing two distinct conjugated polymer nanostructures (CPNs): polythiophene (PEDOT) and polyaniline (PANI). 123 As supported by the in vitro bactericidal assay, both the CPNs were shown to exhibit antimicrobial activity against S. aureus and E. coli under ultraviolet A (UVA) irradiation. However, negligible inhibition of bacterial growth was observed with bulk PEDOT and PANI without light.…”
Section: Synthetic Macromolecule-based Antibiofilm Agentsmentioning
confidence: 98%
“…164 Ghosh et al (2021) showed that two types of conductive polymer nanofibers (CPNs) including polythiophene (PEDOT) and polyaniline (PANI) showed strong antimicrobial activity against E. coli and S. aureus biofilms. 165 The bactericidal activity of these CPNs is attributed to the generation of ROS (reactive oxygen species) induced by photostimulation, which can cause damage to the bacterial cell membranes and subsequently restrict biofilm formation.…”
Section: Metal and Metal Oxidementioning
confidence: 99%